RANCANG BANGUN KNOWLEDGE ACQUISITION BERBASIS WEB SEBAGAI SHARING INFORMASI KEGIATAN MAHASISWA (Studi Kasus: Organisasi UIN Syarif Hidayatullah Jakarta) - Resti Pratama (UIN Syarif Hidayatullah Jakarta, 2017)
The student organization provides a lot of knowledge, and experience is certainly very useful, and has many annual work program plans to implement, not all of its information is known to all students or the public. However, the current system can not be maximized by the student organization, so that the dissemination of information on student activities is less open. The purpose of this research is to design and produce information dissemination system of student activity in order to spread openly and to document knowledge related to certain student organization activity through knowledge management system as information sharing of student activity.